Factors Affecting Preparation Regional Revenue And Expenditure Budget Performance Based In Bima City Government - Sabil, M. Adzan; Afifi, Mansyur; Pitutingsih, Endar (E-Jurnal Akuntansi, 2024)
The purpose of this study is to empirically test and analyze whether the factors of organizational commitment, improvement of the administrative system, sufficient resources, leadership style, participation, rewards and sanctions have an effect on the preparation of the performance-based APBD. The population in this study were all regional work units within the scope of the Bima City Government totaling 27 (twenty-seven) units and the heads of regional work units, heads of sections/fields and heads of sub-sections of programs and reporting in SKPD totaling 115 people as samples. The results of this study prove that partially organizational commitment, leadership style and participation have a positive and significant effect on the preparation of the performance-based APBD in the Bima City Government, while the improvement of the administrative system, sufficient resources, rewards and sanctions have a positive but not significant effect on the preparation of the performance-based APBD in the Bima City Government. The results of this study also prove that 77.80% of the variation in the dependent variable is explained by the independent variable, and the remaining 22.20% is explained by other variables outside the variables used. Keywords: E-Commerce, Accounting Information Systems, Business Capital, Student Interest in Entrepreneurship.